Financial Stability and Spending Habits of Police Officers in the 4th District of Camarines Sur - Barbacena, Krizzia (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the financial stability and spending habits of police officers in the 4th District of Camarines Sur. Anchored on the Hierarchy of Needs Theory, Achieving Society Theory, and Level of Aspiration Theory, the study investigated financial stability in terms of compensation, growth opportunities, and financial security; spending habits based on economic, personal, and social factors; financial stressors related to budgeting constraints and unexpected expenses; and the relationships among these variables. A descriptive-correlational research design was employed using a validated researcher-made questionnaire administered to 193 police officers selected through purposive sampling. Data were analyzed using frequency counts, percentages, weighted mean, and Pearson’s Product-Moment Correlation. The findings revealed that police officers demonstrated a moderately high level of financial stability, with growth opportunities emerging as the strongest dimension, followed by financial security and compensation. Spending habits were likewise moderately influenced by economic, personal, and social factors, with respondents prioritizing emergency savings, essential needs, simple living, and timely payment of obligations. Financial stressors were generally perceived as less serious, although unexpected expenses, particularly medical emergencies, remained the greatest challenge. The study further established a strong and statistically significant relationship between financial stability and spending habits, while budgeting constraints differed between Police Commissioned Officers and Non-Police Commissioned Officers. Based on these findings, the study recommends strengthening financial literacy initiatives, financial management practices, institutional welfare programs, and the implementation of a financial stability and resilience program for police officers. The study supports Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth by promoting financial resilience and responsible financial management among police officers, and SDG 16: Peace, Justice and Strong Institutions by strengthening institutional integrity and effective public service. The findings contribute to socio-economic, institutional, and community sustainability by providing evidence that may guide financial wellness programs, policy development, and organizational support for law enforcement personnel.
Keywords: Compensation; Financial Stability; Financial Stressors; Police Officers; Spending Habits; Sustainability